A case study of the relationship of organizational change and employees' commitment among staff at Sarawak Skills Development Centre, Kuching Sarawak / Nurul Asyikin Mohamad Sabri - Mohamad Sabri, Nurul Asyikin (2017)
The purpose of this study was to determine the level of agreement of Organization Change towards Employees Commitment and to determine the relationship between Organization Change and Employees Commitment Among Staff at Sarawak Skills Development Centre. This study provides important insight about organizational change into various elements of employees‟ commitment which are affective commitment and continuance commitment. This study used quantitative research method which is by distributing questionnaire that was distributed to 108 respondents. Besides, Descriptive and Correlation analysis was used for this study to examine organizational change and employees‟ commitment. The findings showed that the highest level of agreement was organizational change followed by employees‟ commitment. Moreover, there is a significant positive and large relationship between organizational change with employees commitment. Furthermore, the evidence provided in this study supports how organization manages their employees‟ commitment during organization change. Further research for this study was necessary by involving public sector to enhance the researcher to understand more about organizational change and employees‟ commitment.